2021
DOI: 10.3390/medicina57020109
|View full text |Cite
|
Sign up to set email alerts
|

The Role of New Technologies to Prevent Suicide in Adolescence: A Systematic Review of the Literature

Abstract: Background and objectives: Suicide in adolescents represents a major public health concern. To date, a growing number of suicide preventive strategies based on the use of new technologies are emerging. We aimed to provide an overview of the present literature on the use of new technologies in adolescent suicide prevention. Materials and methods: An electronic search was run using the following keywords: Technology OR Technologies OR APP OR Application OR mobile application) AND (Adolescent OR youth OR puberty)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…However, in this systematic review, regardless of the level and depth of engagement by a variety of stakeholders, the methodological quality in over half of the studies, while appropriate, was weak. This is comparable to the quality of evidence produced by traditional research approaches [ 72 , 73 ]. We recommend the investigation of whether, over time, improved approaches to multisectoral collaborations lead to increased use of rigorous research methods, a core principle of co-creation of new knowledge [ 9 ].…”
Section: Implications For Future Researchsupporting
confidence: 54%
“…However, in this systematic review, regardless of the level and depth of engagement by a variety of stakeholders, the methodological quality in over half of the studies, while appropriate, was weak. This is comparable to the quality of evidence produced by traditional research approaches [ 72 , 73 ]. We recommend the investigation of whether, over time, improved approaches to multisectoral collaborations lead to increased use of rigorous research methods, a core principle of co-creation of new knowledge [ 9 ].…”
Section: Implications For Future Researchsupporting
confidence: 54%
“…Ejemeyovwi et al (2019) argued that internet usage plays a significant role in improving human development in 15 Economic Community of West African States (ECOWAS). However, the ICT penetration has both positive and negative societal effect as evident from the literature (Forte et al 2021;UNCTAD 2011;Gunduz 2007;Quaglio and Millar 2020) and a summary of the details is reported in Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there was significant variability in the types of medical and patient-reported outcomes in the studies identified in this review, with notable gaps in critical outcomes like suicide prevention. While some studies show promise in using technology to decrease suicidal ideation and attempts in adolescents, more research is needed on the usage of peer support in these interventions (Forte et al, 2021).…”
Section: Discussionmentioning
confidence: 99%